Peta Pemikiran Politik Islam Modern - Fadhil, Abdul (Jurnal Studi Al-Qur’an, 2012)
The modern political thought in the Islamic world has developed since the Islamic countries came into contact with the Western world, especially when the Islamic world fell into the Western imperialism. There are three factors influencing the contemporary Islamic thought: the decline of the Islamic world caused by the internal factors; the Western harassment toward the integration of political regional power in the Islamic world; and the Western supremacy in science, technology, and organization. Three factors undoubtly influence the orientation of the Islamic political thinkers in facing the new era. However, it is also these three factors that cause the diversity of the Islamic political thoughts with modern perception. How have the Islamic political thinkers behaved to the phenomena? This paper is trying to find out the leading thread of the political patterns that have developed since that era. Keyword : Modern political, Islamic world, western world